PENERAPAN PRINSIP BAGI HASIL PADA BANK SYARIAH DI JAWA TIMUR - Abd. Shomad (Masalah-Masalah Hukum, 2010)
The purposes of this research are to find out knowledge and understanding of PLS-Principle and its application in the operating of Islamic Bank. The type of this research is legal research. By this research showed up that Jointventure Profit Sharing (Musyarakah) is Islamic Law and nationalbanking Law concept Musyarakah is form business arrangement in which a number of partner pool their financial resources to undertaken a commercial industrial enterprise and share in the resulting profits (or losses) corresponding to their share in the financial arrangement maybe applied eitherto the whole form on may have project specific orentation. By this research showed up that Musyarakah be applied in Islamic Banking by some modification to harmonized with the condition of modern banking. That application is not contradict with to principle of Islamic Law.